L2 English Reading, Spelling, and Cognitive-Linguistic Development - Heike Mlakar; Marco Schilk (Language and Literacy: A Canadian Educational e-journal)
This study explores the effects of two two-year literacy intervention programs (phonics and whole word) on L1 German speaking children’s L2 English reading, spelling, and cognitive-linguistic development (N = 49). We assessed reading skills (L2 reading comprehension and fluency), spelling ability (L2 real word and pseudoword accuracy), and cognitive-linguistic skills (working memory, phonological short-term memory, non-verbal intelligence, phonological awareness, L2 receptive grammar, and vocabulary). Based on mixed-effects modeling, phonics instruction led to significantly better L2 real word spelling accuracy and L2 vocabulary knowledge. Phonological short-term memory skills profited from phonics instruction, resulting in significantly higher scores over time.